(3QYGjI GdQYjIs - (3GHf CHj MLIs
(3ChdgG (B:s
(3jHOC Hbhdg CKfGA GdNWHI hCYXegG faYkG hCLeYgG ddNjQGJ CUdG haQYkG s
(3BNQgG (B:s
(3jfJgi HhbaI cGJH BNQgG bhdg (B: (3hbGd GHf CHj MUjfI jeOM GdSdWGf Gdedc GdYOd deG WZi HYV LfS GdcaQ hGQJcHhG eQGcH eKdgG ai GdHMQ de jSQ Je GdcJGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3eUOQ GbJfGA GdCUd (B:s
(3ef GdNRGfI GdedcjI HeOjfI GdQHGW (B(6795) s
Keywords: (3GdSjGSI hGdGLJeGYs